Immunological correlates of mycobacterial growth inhibition describe a spectrum of tuberculosis infection - Matthew K. O’Shea (Nature Portfolio, 2018)
Abstract A major contribution to the burden of Tuberculosis (TB) comes from latent Mycobacterium tuberculosis infections (LTBI) becoming clinically active. TB and LTBI probably exist as a spectrum and currently there are no correlates available to identify individuals with LTBI most at risk of developing active disease. We set out to identify immune parameters associated with ex vivo mycobacterial growth control among individuals with active TB disease or LTBI to define the spectrum of TB infection. We used a whole blood mycobacterial growth inhibition assay to generate a functional profile of growth control among individuals with TB, LTBI or uninfected controls. We subsequently used a multi-platform approach to identify an immune signature associated with this profile. We show, for the first time, that patients with active disease had the greatest control of mycobacterial growth, whilst there was a continuum of responses among latently infected patients, likely related to the degree of immune activation in response to bacillary load. Control correlated with multiple factors including inflammatory monocytes, activated and atypical memory B cells, IgG1 responses to TB-specific antigens and serum cytokines/chemokines. Our findings offer a method to stratify subclinical TB infections and the future potential to identify individuals most at risk of progressing to active disease and benefit from chemoprophylaxis.